Pentachloronitrobenzene Reduces the Proliferative Capacity of Zebrafish Embryonic Cardiomyocytes via Oxidative Stress - Guoqiang Fan; Tianzhu Shen; Kun Jia; Xiaoping Xiao; Zhanfeng Wu; Fanghua Gong; Huiqiang Lu (Toxics, 2022)
Pentachloronitrobenzene (PCNB) is an organochlorine protective fungicide mainly used as a soil and seed fungicide. Currently, there are few reports on the toxicity of PCNB to zebrafish embryo. Here, we evaluated the toxicity of PCNB in aquatic vertebrates using a zebrafish model. Exposure of zebrafish embryos to PCNB at concentrations of 0.25 mg/L, 0.5 mg/L, and 0.75 mg/L from 6 hpf to 72 hpf resulted in abnormal embryonic development, including cardiac malformation, pericardial edema, decreased heart rate, decreased blood flow velocity, deposition at yolk sac, shortened body length, and increased distance between venous sinus and arterial bulb (SV-BA). The expression of genes related to cardiac development was disordered. However, due to the unstable embryo status in the 0.75 mg/L exposure concentration group, the effect of PCNB on the expression levels of cardiac-related genes was not concentration-dependent. We found that PCNB increased reactive oxygen species stress levels in zebrafish, increased malondialdehyde (MDA) content and catalase (CAT) activity, and decreased superoxide dismutase (SOD) activity. The increased level of oxidative stress reduced the proliferation ability of zebrafish cardiomyocytes, and the expressions of zebrafish proliferation-related genes such as cdk-2, cdk-6, ccnd1, and ccne1 were significantly down-regulated. Astaxanthin (AST) attenuates PCNB-induced reduction in zebrafish cardiomyocyte proliferation by reducing oxidative stress levels. Our study shows that PCNB can cause severe oxidative stress in zebrafish, thereby reducing the proliferative capacity of cardiomyocytes, resulting in zebrafish cardiotoxicity.